Neuroprotective effects of flavone luteolin in neuroinflammation and neurotrauma. (24th October 2020) - Kempuraj, Duraisamy; Thangavel, Ramasamy; Kempuraj, Deepak D.; Ahmed, Mohammad Ejaz; Selvakumar, Govindhasamy Pushpavathi; Raikwar, Sudhanshu P.; Zaheer, Smita A.; Iyer, Shankar S.; Govindarajan, Raghav; Chandrasekaran, Premkumar Nattanmai; Zaheer, Asgar
Abstract: Neuroinflammation leads to neurodegeneration, cognitive defects, and neurodegenerative disorders. Neurotrauma/traumatic brain injury (TBI) can cause activation of glial cells, neurons, and neuroimmune cells in the brain to release neuroinflammatory mediators. Neurotrauma leads to immediate primary brain damage (direct damage), neuroinflammatory responses, neuroinflammation, and late secondary brain damage (indirect) through neuroinflammatory mechanism. Secondary brain damage leads to chronic inflammation and the onset and progression of neurodegenerative diseases. Currently, there are no effective and specific therapeutic options to treat these brain damages or neurodegenerative diseases. Flavone luteolin is an important natural polyphenol present in several plants that show anti‐inflammatory, antioxidant, anticancer, cytoprotective, and macrophage polarization effects. In this short review article, we have reviewed the neuroprotective effects of luteolin in neurotrauma and neurodegenerative disorders and pathways involved in this mechanism. We have collected data for this study from publications in the PubMed using the keywords luteolin and mast cells, neuroinflammation, neurodegenerative diseases, and TBI. Recent reports suggest that luteolin suppresses systemic and neuroinflammatory responses in Coronavirus disease 2019 (COVID‐19). Studies have shown that luteolin exhibits neuroprotective effects through various mechanisms, including suppressing immune cell activation, such as mast cells, and inflammatory mediators released from these cells. In addition, luteolin can suppress neuroinflammatory response, activation of microglia and astrocytes, oxidative stress, neuroinflammation, and the severity of neuroinflammatory diseases such as Alzheimer's disease, Parkinson's disease, multiple sclerosis, and TBI pathogenesis. In conclusion, luteolin can improve cognitive decline and enhance neuroprotection in neurodegenerative diseases, TBI, and stroke. Abstract : Flavone luteolin is an important natural polyphenol present in several plants that show anti‐inflammatory, antioxidant, anticancer, cytoprotective, and macrophage polarization effects. In this short review article, we have reviewed the neuroprotective effects of luteolin in neurotrauma/traumatic brain injury (TBI) and neurodegenerative disorders and pathways involved in this mechanism. We suggest that luteolin can improve cognitive decline and enhance neuroprotection in neurodegenerative diseases and neurotrauma/TBI conditions.